2017
DOI: 10.18632/oncotarget.22200
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reverses bFGF-induced epithelial-mesenchymal transition in HCC cells

Abstract: Metformin had exerted important inhibitory effects in multiple cancers. However, the correlation between metformin and hepatocellular carcinoma (HCC) metastasis, and the relevant mechanisms are still unclear. By quantitative proteomics analysis technique, we found metformin could suppress FGF signalling significantly. In FGF signalling basic fibroblast growth factor (bFGF) is a crucial member, it initially binds to its receptors, the complex of bFGF and receptors activate FGF signallings, and promote many canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…Notably, bFGF antisense oligonucleotide therapy shows that it can prevent the development of pulmonary fibrosis in animals [38], suggesting that bFGF stimulates lung fibrosis and it is a important target for lung fibrosis therapy. The downstream effectors of bFGF were phosphatidylinositol 3-kinase (PI3K), mitogen-activated kinases, protein kinase B (Akt) and glycogen synthase kinase 3β (AKT/GSK-3β), and PI3K/Akt and AKT/GSK-3β pathways were obviously activated in bFGF-induced EMT [16,39,40], and when PI3K/Akt was blocked, the effects of bFGF on EMT were weakened [41]. Thus, we speculated that the bFGF-PI3K/Akt signaling pathway also play an important role in BLM-induced EMT, which is classified as a non-Smad signaling pathway.…”
Section: Bfgf Promoted Emt Via Pi3k/akt Signaling Pathways In Bleomycmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, bFGF antisense oligonucleotide therapy shows that it can prevent the development of pulmonary fibrosis in animals [38], suggesting that bFGF stimulates lung fibrosis and it is a important target for lung fibrosis therapy. The downstream effectors of bFGF were phosphatidylinositol 3-kinase (PI3K), mitogen-activated kinases, protein kinase B (Akt) and glycogen synthase kinase 3β (AKT/GSK-3β), and PI3K/Akt and AKT/GSK-3β pathways were obviously activated in bFGF-induced EMT [16,39,40], and when PI3K/Akt was blocked, the effects of bFGF on EMT were weakened [41]. Thus, we speculated that the bFGF-PI3K/Akt signaling pathway also play an important role in BLM-induced EMT, which is classified as a non-Smad signaling pathway.…”
Section: Bfgf Promoted Emt Via Pi3k/akt Signaling Pathways In Bleomycmentioning
confidence: 99%
“…Moreover, bFGF acts as a potent mitogen that stimulates the proliferation, differentiation and migration of mesenchymal cells [14]. In addition, in both hepatocellular carcinoma (HCC) and prostate cancer cells, bFGF was shown to induce epithelial-mesenchymal transition through the AKT/GSK-3β/Snail signaling pathway [15,16]. Although it has been reported that bFGF can induce EMT, the definite process remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ferritti et al suggested that metformin suppress the migration and invasion of hepatocellular carcinoma cells dependent on AMPK activation [99]. This effect of metformin was related to its blockade on bFGF-induced Akt/GSK activation, and subsequent Twist1 stabilization [100]. Meanwhile, metformin repressed HCC metastasis through inhibiting tumor angiogenesis.…”
Section: Ampk Activators In Hcc Treatmentmentioning
confidence: 99%
“…Metformin induced Snail ubiquitination after LKB1 phosphorylation, which helped Snail's interaction with E3 ligase FBXL14 [44]. Furthermore, metformin decreased Twist with obliterating interaction between GSK-3β and Twist via reducing Akt/GSK-3β pathway [45]. mTOR, of which inhibition under metformin therapy mediated suppression of HIF-1α/VEGF-A and p70s6k [46,47], was another downstream molecule of Akt.…”
Section: Discussionmentioning
confidence: 99%